Microscopic impactor debris at Kamil Crater (Egypt): The origin of the Fe-Ni oxide spherules. (15th October 2022) - Folco, L.; Carone, L.; D'Orazio, M.; Cordier, C.; Suttle, M.D.; van Ginneken, M.; Masotta, M.
Abstract: Kamil crater (Egypt) is a natural laboratory for the study of processes and products associated with the impacts of small iron projectiles on the Earth's crust. In particular, because of the distinctive composition of the impactor (an ungrouped Ni-rich ataxite) and the target (Cretaceous sandstones and minor wackes) it offers a unique opportunity to study impactor–target physical–chemical interactions. Continuing the study of impact melt ejecta, we investigated the mineralogy and geochemistry of 25 Fe-Ni spherules - representative of a suite of 135 - recovered from the soil around the crater. Samples were collected during our 2010 geophysical expedition and investigated by combining scanning electron microscope imaging, electron probe microanalyzer and Raman spectroscopy analyses. Spherules range in size from 100 to 500 µm and show a variety of dendritic textures and mineral compositions dominated by Fe-Ni oxides of the wüstite – bunsenite and magnetite – trevorite series or Fe-Ni metal. All these features indicate quenching of high temperature (1600–1500 °C) oxide or metal liquid droplets under varying oxidizing conditions. A geochemical affinity with the iron impactor recorded by the Fe, Co, Ni ratios in the constituent phases (average Ni/Co element ratio of 25.1 ± 7.6; average Ni/(Ni + Fe) molar ratio of 0.21 ± 0.13), combined with target contamination (i.e., the ubiquitous occurrence of Si and Al from trace to minor amounts), document their origin as impact melt spherules formed through the physical and chemical interaction between metal projectile and silicate target melts and air. We propose a petrogenetic model that envisions formation as liquid droplet residues of immiscible projectile in a mixed silicate melt and their subsequent separation as individual spherules by stripping during hypervelocity ejection. We also argue that this model applies to all impact events produced by small iron projectiles and that such individual Fe-Ni oxide and metal spherules should be common impact products, despite little documentation in the literature. Our detailed mineralogical and geochemical characterization will facilitate their distinction from other, similar spherules of different origin (cosmic spherules, ablation spherules) often encountered in the geologic record.